Faktor-faktor utama yang mempengaruhi dalam membuat keputusan peruntukan pelaburan harta tanah dari perspektif pelabur. (Kes kajian : syarikat harta tanah di Malaysia) - Mukhatar, Norul-Ainin (2005)
Property investment activities in developers and investments companies such as I&P, HLPB, Bolton, SP Setia, Mui Properties, Kejora Harta, Talam Corporation and Mutiara Goodyear be able to diversify the investment portfolio and increase their income in long term. However, the allocation of real estate investment activities is always exchange because of the some important factors. The study has two objectives which are 1) to determine the activities of the investor and developers companies in Malaysia 2) to determine the important factors that influence in order to developed an optimal asset allocation model from the investors perspectives. This study was undertaken in real estate development and investment. The questioners have been distributed to the respective respondents in real estate developers and investment. The methods of frequency and descriptive analysis have been used to analysis the data. The study has disclosed a number of important findings. First, many of the developers companies in Malaysia were involved in development activities. They involved to developed residential and office building. Second, give good return is the most important factors that influence in order to develop an optimal asset allocation model from the investor’s perspectives. The study also recommended the strategic planning in order to allocate an optimal asset allocation companies